Russia’s Use of Autonomous Weapon Systems: An Analysis of Offensive Military Policy in the 2022–2024 Russia-Ukraine War - Mewoh, Glory; Yanuar Rahmadan (Politeia : Journal of Public Administration and Political Science and International Relations, 2025)
The development of artificial intelligence (AI) technology has brought significant changes to the defense sector, particularly through the emergence of autonomous weapon systems. In this context, major countries are competing to harness the potential of AI to enhance their military capabilities, including Russia, which has shown significant progress in integrating AI into its defense policy especially amid rising geopolitical tensions. This study aims to analyze the main factors driving Russia to develop AI-based autonomous weapon systems as part of its military policy during the Russia-Ukraine conflict in the period 2022–2024. Using qualitative methods and a literature review approach, this research processes secondary data from various relevant official and academic sources, including defense reports, peer-reviewed journals, military analyses by experts, and interviews published by credible international media outlets. To better understand Russia's strategic direction, this study uses the Offense-Defense Balance (ODB) Theory, which explores how shifts in dominance between offensive and defensive capabilities affect the likelihood of conflict escalation. This theoretical framework helps explain how technological advances particularly in artificial intelligence (AI)-based weapon systems can alter the military balance and drive more aggressive strategies. Theoretically, this study contributes to the expansion of the application of ODB Theory in AI-driven warfare. Practically, it provides insights into Russia's military modernization efforts and their broader implications for global security, both in the short and long term, within an increasingly complex and unpredictable international landscape.